« Je viens d’achever le billet que j’avais dans la tête » - Adrien Rannaud (Contextes)
The text highlights the principles of circularity and contamination between French Canadian Michelle Le Normand’s diary writing and journalism. It works at retracing a significant interdependence between the diary and the periodical, regarded as writing laboratories. The paper discusses how this interdependence processes the diary form of narrative into an autobiographical story that first appeared in newspapers, then in books. It leads to reflect on the state of the genre/gender imaginary (Christine Planté) in Québec literature during the first half of the 20th century.